Transcriptomic analysis of cell envelope inhibition by prodigiosin in methicillin-resistant Staphylococcus aureus - Liu, Xiaoxia; Wang, Zonglin; You, Zhongyu; Wang, Wei; Wang, Yujie; Wu, Wenjing; Peng, Yongjia; Zhang, Suping; Yun, Yinan; Zhang, Jin (Frontiers in Microbiology, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a leading threat to public health as it is resistant to most currently available antibiotics. Prodigiosin is a secondary metabolite of microorganisms with broad-spectrum antibacterial activity. This study identified a significant antibacterial effect of prodigiosin against MRSA with a minimum inhibitory concentration as low as 2.5 mg/L. The results of scanning electron microscopy, crystal violet staining, and confocal laser scanning microscopy indicated that prodigiosin inhibited biofilm formation in S. aureus USA300, while also destroying the structure of the cell wall and cell membrane, which was confirmed by transmission electron microscopy. At a prodigiosin concentration of 1.25mg/L, biofilm formation was inhibited by 76.24%, while 2.5 mg/L prodigiosin significantly reduced the vitality of MRSA cells in the biofilm. Furthermore, the transcriptomic results obtained at 1/8 MIC of prodigiosin indicated that 235and 387 genes of S. aureus USA300 were significantly up-and downregulated, respectively. The downregulated genes were related to two-component systems, including the transcriptional regulator LytS, quorum sensing histidine kinases SrrB, NreA and NreB, peptidoglycan biosynthesis enzymes (MurQ and GlmU), iron-sulfur cluster repair protein ScdA, microbial surface components recognizing adaptive matrix molecules, as well as the key arginine synthesis enzymes ArcC and ArgF. The upregulated genes were mainly related to cell wall biosynthesis, as well as twocomponent systems including vancomycin resistance-associated regulator, lipoteichoic acid biosynthesis related proteins DltD and DltB, as well as the 9 capsular polysaccharide biosynthesis proteins. This study elucidated the molecular mechanisms through which prodigiosin affects the cell envelope of MRSA from the perspectives of cell wall synthesis, cell membrane and biofilm formation, providing new potential targets for the development of antimicrobials for the treatment of MRSA.